Visceral adiposity index and insulin secretion and action in first‐degree relatives of subjects with type 2 diabetes. Issue 3 (4th February 2015) - Yang, Yumei; Feng, Yan; Ma, Xuesong; Chen, Kaiting; Wu, Nannan; Wang, Dongmei; Li, Pengjie; Wang, Minnan; Li, Qiang; Zhang, Jinchao
Abstract Background To explore the predictive performance of the newly established visceral adiposity index for diabetes and prediabetes, as well as the relationships between the visceral adiposity index and the parameters of insulin secretion and action. Methods Eight hundred twenty‐four first‐degree relatives of individuals with type 2 diabetes who had no known history of abnormal glucose regulation were selected. Diabetes and prediabetes were diagnosed using the standard oral glucose tolerance test. Results The visceral adiposity index values were greater for the subjects with prediabetes and diabetes than for those with normal glucose regulation. Among the subjects with normal glucose regulation, the visceral adiposity index was higher for those whose levels were above the median value of the incremental area under the curve for glucose than for the subjects whose levels fell below the median value. The visceral adiposity index was negatively correlated with the homeostasis model assessment of the β‐cell function index (Homa‐β) and with the insulinogenic index (ΔI30/ΔG30). The visceral adiposity index was found to be a valuable predictor of diabetes, but it was not superior to triglyceride levels, waist circumference, or lipid accumulation production. Conclusions The first degree relatives of people with type 2 DM who have prediabetes or diabetes have progressively higher visceral adiposity index in association with progressive hyperglycemia, and it was found to correlate with the Homa‐β and the ΔI30/ΔG30. Copyright © 2014 John Wiley & Sons, Ltd.